2014
DOI: 10.1164/rccm.201407-1290le
|View full text |Cite
|
Sign up to set email alerts
|

Using Exhaled Nitric Oxide and Serum Periostin as a Composite Marker to Identify Severe/Steroid-Insensitive Asthma

Abstract: Definition of abbreviations: ACT = asthma control test; ECP = eosinophil cationic protein; F = female; FE NO = exhaled nitric oxide; hsCRP = high-sensitivity C-reactive protein; ICS = inhaled corticosteroids; IgE = immunoglobulin E; M = male. Results are presented as means 6 SD, except for IgE [medians (ranges)]. *Number of patients, n = 57; elevated FE NO is defined as equal to or greater than 25 ppb; serum periostin levels are defined using 95 ng/ml as the cutoff point. † Patients who had smoked more than 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 15 publications
0
37
0
Order By: Relevance
“…FeNO, another surrogate biomarker for type 2 immunity, is also correlated with serum periostin 4144. Nagasaki et al44 showed that the correlation between FeNO and serum periostin is much stronger in patients with severe asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FeNO, another surrogate biomarker for type 2 immunity, is also correlated with serum periostin 4144. Nagasaki et al44 showed that the correlation between FeNO and serum periostin is much stronger in patients with severe asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Nagasaki et al44 showed that the correlation between FeNO and serum periostin is much stronger in patients with severe asthma.…”
Section: Introductionmentioning
confidence: 99%
“…49 Additionally, we have recently found that FeNO was moderately to strongly associated with serum periostin in step 4/5 patients, but only weakly in the overall patients. 50 As mentioned before, FeNO is another biomarker of type 2 immune responses. 51,52 Taken together, these results verified that serum periostin is a surrogate biomarker of type 2 immune responses.…”
Section: Periostin As a Surrogate Biomarker Of Type 2 Immune Responsesmentioning
confidence: 92%
“…Serum periostin levels also correlated with fractional exhaled nitric oxide (FE NO ) and with airway hyperresponsiveness to methacholine and mannitol in asthmatic children [24]. More importantly, high serum periostin in patients with high FE NO was a risk for subsequent asthma exacerbations despite taking high-dose ICS, independent of known risks including low FEV 1 [25]. Importantly, circulating periostin levels seemed to be stable within subjects at 3 measurements in a 5-week period [21].…”
Section: Introductionmentioning
confidence: 93%